ANALISIS PENYIRAMAN AIR KERAS KEPADA NOVEL BASWEDAN DALAM TINJAUAN PEMIKIRAN ETIKA BURRHUS FREDERIC SKINNER - mirelda, adiva; Putra Erawan, I Ketut; Radita Novi Pospitasari, Ni Wayan (Jurnal Nawala Politika, 2023)
On April 11 2017, while walking home after morning prayers at the mosque, former KPK chairman Novel Baswedan was suddenly doused with acid by two unknown men riding a motorbike. Since then, Novel has undergone a series of treatments to heal his eyes. Since 2017, the police have formed a team containing hundreds of personnel from the police, regional police assisted by the National Police Headquarters. However, the team's independence is in doubt and it is thought that it will not have a significant impact on the development of Novel's case. The management of the joint team is dominated by police officials, from the National Police Chief, General Tito Karnavian, to the Deputy Chief of Metro Jaya Police, Brigadier General Wahyu Hadiningrat. According to Burrhus Frederic Skinner, the "stimulus-answer" scheme is too simple for the thinking of the Russian psychologist, Ivan Petrovitsh Pavlov. This thinking is naturally based on an instinctual structure which itself is based on genetic structure, organisms react (reflex) in a unique way to certain stimuli. This understanding of "conditioned reflexes" is a key behaviorist understanding. Then from here the behavior of the individual who sprinkled acid on the former chairman of the KPK, Novel Baswedan, can be determined as a stimulus and the answer to why he carried out this action and what results he wanted to achieve.